PERSEPSI PESERTA DIDIK MENGENAI PELAKSANAAN PEMBELAJARAN GURU SEJARAH DI MADRASAH ALIYAH MATHLA'UL ANWAR PONTIANAK - Lesti, Lesti; Aminuyati, Aminuyati; Chalimi, Ika Rahmatika (Universitas Tanjungpura, 2023)
This research aims to determine the perceptions of students regarding the implementation of history teacher learning at Madrasah Aliyah Mathla'ul Anwar Pontianak. This research used a qualitative method with a descriptive approach. Sources of data in this study were teachers of history subjects, students, and RPP documents. The Data collection techniques used observation, interviews, and documents. The Data collection tools used observation guidelines, interview guidelines, and documentation. The Data analysis used data reduction, data presentation, and conclusions. The results of this research showing to (1) The Preliminary activities of learning implementation have been carried out by the teacher in accordance with the lesson plans and the answers of some of the teacher students have carried out preliminary activities. (2) The core activities of learning implementation have been carried out by the teacher although there are activities that are sometimes not carried out in learning but learning continues to run smoothly. (3) The closing activities of the learning implementation have been carried out by the teacher in accordance with the lesson plans and are also supported by the answers of several students that the teacher has carried out closing activities in learning